The nighttime anomalies using Global IGS VTEC Maps - Natali, Maria Paula (2013)
In this paper we show the VTEC variations at night, considering their geomagnetic, seasonal and solar activity dependences. The variations are analyzed in two time periods 10 p.m. (pre-midnight) and 2 a.m. (post-midnight); and for two different solar conditions; one during high solar activity (2000) and the other during low solar activity (2008). Spatial and temporal ionosphere variability is investigated from Global IGS VTEC maps applying Principal Component Analysis (PCA). The IGS VTEC maps are reorganized and from each daily global dataset, two maps were constructed one at 10 p.m. and the other at 2 a.m. From these two series of VTEC maps covering periods low and high solar activity for each local time we found that: (1) The pre-midnight (10 p.m.) VTEC variability presents a strong semiannual anomaly at equatorial and low geomagnetic latitudes during high solar activity and in low solar activity an annual variation with maximum in summer at low-mid geomagnetic latitude. (2) The post-midnight (2 a.m) VTEC variability shows an annual variation at low and high solar activity, except in the equatorial region for high solar activity where a semiannual variation is recorded (the amplitude is twice lower than the amplitude at pre-midnight). The winter anomaly is present in the northern hemisphere in the American longitude sector and in the north-east of Africa; and a very small region in the south-west of Oceania.